ASSESSMENT OF THE DIAGNOSTIC VALUE OF SERUM CATHEPSIN S AND ITS CORRELATION WITH HDL SUBCLASSES IN PATIENTS WITH NON-HODGKIN’S LYMPHOMA : Cathepsin S and HDL subclasses in lymphoma - Mirjanić-Azarić, Bosa; Stankovic, Sinisa; Radic Savic, Zana; Malcic-Zanic, Dragana; Ninic, Ana; Vukovic, Marija; Nezic, Lana; Skrbic, Ranko; Bogavac-Stanojevic, Natasa (Journal of Medical Biochemistry, 2024)
Background: Recent findings point to the key role of cathepsin S (CTSS) in the survival of malignant cells, as well as the significance of the anti-apoptotic properties of high-density lipoprotein (HDL) that contribute to enhanced cell survival. The purpose of this study is to analyze CTSS as a potential biomarker in lymphoma. Also, in order to better understand the role of CTSS in the origin and development of lymphoma, its association with cystatin C (Cys C), lipids, and inflammatory markers was analyzed. Methods: The study included 90 subjects: 11 Hodgkin (HL) and 44 B-cell non-Hodgkin lymphoma (NHL) patients, and 35 healthy subjects. CTSS was determined using the Invitrogen ELISA kit (Thermo Fisher Scientific, Inc., Waltham, MA, USA). Results: The level of CTSS was significantly higher in NHL patients than in control subjects: 12.20 (9.75-14.57) vs 9.97 (8.44-10.99), P<0.001. In NHL patients, there was a positive correlation between CTSS and the proportions of HDL3a, HDL3b, and the sum of the HDL3 subclasses (r=0.506, P<0.001; r=0.411, P=0.006, r=0.335, P=0.026, respectively). In addition, the area under the receiver operating characteristic curve (AUC curve) of CTSS was 0.766 (CI: 0.655-0.856). Conclusions CTSS is significantly elevated in patients with NHL and has the potential to be a new diagnostic biomarker. Moreover, demonstrating a correlation between CTSS levels and the proportion of anti-apoptotic HDL3a and HDL3b subclasses improves understanding of NHL, as well as contributes to the development of new therapeutic strategies for this cancer.